2009
DOI: 10.1124/jpet.109.162164
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine, in Part through Tumor Necrosis Factor α Inhibition, Prevents Cognitive Decline and β-Amyloid Accumulation in a Mouse Model of Alzheimer's Disease

Abstract: Alzheimer's disease (AD), the most common form of dementia in the older people, is a multifactoral pathology, characterized by cognitive deficits, increase in cerebral deposition of the ␤-amyloid (A␤) peptide, neurofibrillary tangles, and neurodegeneration. Studies currently support a central role of neuroinflammation, through production of proinflammatory cytokines including excess tumor necrosis factor ␣ (TNF-␣) in the pathogenesis of AD, especially in A␤-induced cognitive deficits. Imipramine, a tricyclic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 39 publications
4
53
0
Order By: Relevance
“…17 We observed increases in APP processing and amyloidogenic pathway (C99 levels) in the frontal cortex at all time points, in the amygdala after 3 weeks, and in the hippocampus mainly after 1 and 2 weeks. We therefore confirmed the A␤ [25][26][27][28][29][30][31][32][33][34][35] influence on seeding of endogenous A␤ 1-40/42 proteins in the rodent brain, particularly highlighting differences over time and among structures.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…17 We observed increases in APP processing and amyloidogenic pathway (C99 levels) in the frontal cortex at all time points, in the amygdala after 3 weeks, and in the hippocampus mainly after 1 and 2 weeks. We therefore confirmed the A␤ [25][26][27][28][29][30][31][32][33][34][35] influence on seeding of endogenous A␤ 1-40/42 proteins in the rodent brain, particularly highlighting differences over time and among structures.…”
Section: Discussionmentioning
confidence: 67%
“…15 Deposits of A␤ [25][26][27][28][29][30][31][32][33][34][35] peptide after its injection have not yet been characterized by IHC, for lack of specific and selective antibodies. However, Klementiev et al 16 and Chavant et al 17 reported an accumulation of A␤ immunolabeling in the hippocampus and cerebral cortex, induced 4 and 2 weeks, respectively, after the A␤ [25][26][27][28][29][30][31][32][33][34][35] injection. In the present study, we followed over time the cerebral localization of A␤ [25][26][27][28][29][30][31][32][33][34][35] after injection into the lateral ventricle by using an A␤ [25][26][27][28][29][30][31][32][33][34][35] -HLF-tagged peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity induced after such central injection of the Ab 25-35 fragment in oligomeric form in mice and rats was repeatedly shown to result in neuroinflammation and reactive gliosis, pro-apoptotic caspases activity, oxidative stress, reduction in the number of neurons measured in hippocampal pyramidal cell layers, loss of cholinergic neurons, and memory deficits (Maurice et al, 1996;Delobette et al, 1997;Stepanichev et al, 2003Stepanichev et al, , 2004Stepanichev et al, , 2006Meunier et al, 2006;Klementiev et al, 2007;Chavant et al, 2010;Villard et al, 2009Villard et al, , 2011Zussy et al, 2011). It is at present widely used to detect the neuroprotective potential of new drugs and natural derivatives (Ruan et al, 2010;Kim et al, 2011;Lu et al, 2012;Wang et al, 2012;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the Ab 25-35 injection resulted not only in an aggressive amyloid toxicity but also in accumulation of endogenous Ab species and Tau hyperphosphorylation, as observed in AD physiopathology. One week after Ab [25][26][27][28][29][30][31][32][33][34][35] injection, APP and Ab 1-42 levels were increased in the hippocampus and cortex, Ab-expressing cells could be visualized using immunohistochemistry and b-secretase cleavage products, such as the C-terminal fragment C99, could be detected (Klementiev et al, 2007;Chavant et al, 2010;Zussy et al, 2011). Moreover, an increase in Tau phosphorylation on physiological or AD-related pathological epitopes induced by Ab 25-35 injection in mice was reported in several studies (Dudas et al, 2002;Klementiev et al, 2007;Deng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%